Editor’s Welcome - Lorna Pairman; Angad S Chauhan (New Zealand Medical Student Journal)
This special issue celebrates 20 years of NZMSJ publication, making us one of the longest-running medical student journals internationally. We aim to continue to support medical student research by publishing open access and free of charge, ensuring publication remains accessible to all medical students.